Impact of heart magnetic resonance imaging on chelation choices, compliance with treatment and risk of heart disease in patients with thalassaemia major. (16th August 2013) - Origa, Raffaella; Danjou, Fabrice; Cossa, Stefano; Matta, Gildo; Bina, Patrizio; Dessì, Carlo; Defraia, Elisabetta; Foschini, Maria L.; Leoni, GiovanBattista; Morittu, Maddalena; Galanello, Renzo
Summary This study aimed to verify the impact of heart magnetic resonance imaging on chelation choices and patient compliance in a single‐institution cohort as well as its predictive value for heart failure and arrhythmias. Abnormal cardiac T2* values determined changes in treatment in most subjects. Heart T2* was confirmed to be highly predictive over 1 year for heart failure and arrhythmias. The choice of chelation regimens known to remove heart iron efficiently was not sufficient by itself to influence the risk. Compliance with treatment had a more remarkable role.